Building resilience, emotional regulation, kindness, and critical thinking in the digital age: An evaluation of the Superpowers Program on Philippine kindergarteners - Rebekah Luo; Sundance Zhihong Sun; Emma Carter; Therese N Hopfenbeck (International Journal of Educational Research Open)
This study aimed to evaluate via teacher and parent perceptions the impact of the Superpowers Program, designed to enhance social-emotional learning (SEL) and digital literacy among kindergarten children in the Philippines. Limited research has been conducted on young children’s online exposure in less-developed countries. The program focused on developing 12 character strengths that every child needs to navigate their online and offline lives. Employing a mixed-methods approach, the study utilized a single-group pre-post design to evaluate teachers’ and parents’ perceived impact of the program on the development of four selected character strengths (resilience, emotional regulation, kindness and critical thinking), based on quantitative and qualitative data. Quantitative data were collected through self-reported teacher observations using the Character Strengths Survey, while qualitative data were gathered from Focus Group Discussions. Rasch analysis confirmed satisfactory psychometric properties of the survey instrument. Latent regression analysis revealed significant improvements across all character strength scales post-intervention, with qualitative findings corroborating results. Linear regression analyses highlighted significant perceived impacts of children’s pre-intervention abilities, teacher implementation practices, and teacher-parent interactions in the observed positive outcomes of the intervention. These findings suggest that structured SEL and digital literacy programs can effectively promote character strengths crucial for navigating the digital age among young children in developing countries. However, limitations including the small sample size, single-group design and self-report measures necessitate cautious interpretation. The study underscores the potential of integrated SEL and digital literacy programs in early childhood education, while emphasizing the need for cultural adaptation and strong home-school partnerships in their implementation.